Peningkatan Pengetahuan Tentang Gizi Balita pada Ibu Balita untuk Pencegahan Stunting di RS PKU Muhammadiyah Gombong - Juni Sofiana; Hastin Ika Indriyastuti; Umi Sulasih (Prosiding University Research Colloquium, 2022)
Stunting is one of the health problems that Indonesia is still facing. The World Health Organization (WHO) once placed Indonesia as the third country with the highest prevalence of stunting in Asia in 2017. Stunting is a condition of failure to thrive in children under five due to chronic malnutrition, especially in the First 1,000 Days of Life (HPK). Stunting affects the growth and development of the brain so that there is a higher risk of suffering from chronic diseases in adulthood. The purpose of this community service is to increase knowledge to mothers of toddlers about toddler nutrition. This community service method is to conduct counseling about toddler nutrition. Community service results: Pretest results show that of the 15 mothers of children under five who participated in the activity, 11 mothers had less knowledge, and 4 had sufficient knowledge. The results of the posttest after the counseling were 15 mothers of toddlers who had good knowledge. The conclusion of community service is: There is an increase in knowledge after counseling on toddler nutrition